2022
DOI: 10.1186/s12872-022-02747-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ferroptosis-related genes in coronary atherosclerosis and identification of key genes: integration of bioinformatics analysis and experimental validation

Abstract: Background Coronary atherosclerosis (CA) is the most common type of atherosclerosis. However, the inherent pathogenesis and mechanisms of CA are unclear, and the relationship with ferroptosis-related genes (FRGs) has not been reported. The purpose of this study was to use bioinformatics techniques to evaluate potential therapeutic targets for CA.Please provide the given name for author “Dingshun”.Please provide the given name for author “Dingshun”. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Ferroptosis is a newly discovered mode of programmed cell death. In recent years, studies from autopsies and animal experiments have reported that ferroptosis is extensively involved in the development and progression of atherosclerosis (25)(26)(27). Evidence from clinical researches suggested that HMOX1, a key gene of ferroptosis, is strongly associated with the prognosis of patients with atherosclerosis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a newly discovered mode of programmed cell death. In recent years, studies from autopsies and animal experiments have reported that ferroptosis is extensively involved in the development and progression of atherosclerosis (25)(26)(27). Evidence from clinical researches suggested that HMOX1, a key gene of ferroptosis, is strongly associated with the prognosis of patients with atherosclerosis (28).…”
Section: Discussionmentioning
confidence: 99%
“…Biological function analysis showed that ASDEGs was signi cantly enriched in MAPK signal pathway, HLTV-1 infection, osteoclast differentiation and cytokine-cytokine receptor interaction signal pathway [23].…”
Section: Veri Cation Of Core Gene Single Cell Datamentioning
confidence: 99%